Solar cells absorption viewpoint of Mie theory: Experimental analysis of TiO2 doping V/Ce. (2022) - Shanmugan, S.; Selvaraju, P.; Sivakumar, S.; Nagaraj, J.; Srinivas Prasad, M.V.V.K.; Abhiram, N.
Highlights: The highly capable DSC has characterized using CeVTiO2 . The factor absorption of power density results is discussed of AFM. Enhancement of CeVTiO2 powder films is observed in energy wavelength range of 520 nm. CeVTiO2 photocurrent is occupied an absorption efficiency of 44.2%, 24.1% and 8.6%. Overall efficiency of 8% has been achieved by the sample. Abstract: Current effort able to dye-sensitized solar cell (DSC) is effectively considered by TiO2 mixture Ceramic (Ce) / Vanadium (V) (CeVTiO2). The powder films of a CeVTiO2 studied in spectroscopies agree to take to Mie theory, respectively. The new samples analyzed a morphology study XRD values, TEM, and SEM. Electrical, optical properties of doping nanoparticles were considered in GC–MS chemical compounds by the view of Mie theory. The atomic force microscopy (AFM) is measured by the fill factor absorption of the samples. An experimental energy wavelength is 520 nm. Photocurrent absorption to a sample with efficiency is 44.2%, 24.1% and 8.6% and overall performance is 8% with new samples showed in benefit of the potential materials by a solar cell.